MORALITAS, PENGENDALIAN INTERNAL DAN GENDER DALAM KECENDERUNGAN TERJADINYA FRAUD - Merawati, Luh Komang; Mahaputra, I Nym Kusuma Adnyana (Jurnal Akuntansi, 2017)
Morality, Internal Control and Gender in Fraud.University is an economic entity which is required to be accountable and transparent in funds management. Accountability can be indicated through financial reporting that is free from fraud. Fraud refers to the intentionally accounting errors to mislead the financial statement readers and usersin order to taking advantages. This research conducted with research design experiments 2x2 factorial by adding a gender perspective in examining the tendency of commit accounting fraud between individuals who have a (high or low) level of moral reasoning and (with or without) elements of internal control organization as factors that could cause accounting fraud. Data was analyze with two-ways ANOVA and Mann Whitney test in testing hypotheses. Research results indicate significant differences in the tendency of the accounting fraud due to the level of morality, internal control and gender. The results of this study are expected to provide recommendations in evaluating internal control policy to prevent fraudulent accounting practices and the importance of ethics and character education in the university environment to reduce the intention of fraud.